2020
DOI: 10.3389/fpsyt.2020.00593
|View full text |Cite
|
Sign up to set email alerts
|

Null Effect of Olfactory Training With Patients Suffering From Depressive Disorders—An Exploratory Randomized Controlled Clinical Trial

Abstract: Due to a close functional relation between brain areas processing emotion and those processing olfaction, major depression is often accompanied by reduced olfactory function. Such hyposmia can be improved by regular olfactory training (OT) over several months. As this training furthermore improves subjective well-being, we explored whether OT is a useful complementary strategy for depression treatment. A total of 102 depressive outpatients were randomly assigned to OT or a control training condition, which wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 65 publications
0
10
2
Order By: Relevance
“…However, according to the previously mentioned scale, a signi cant percentage of the present sample (one-third of the entire sample) was classi ed as depressed. That could probably explain why the depression severity before and after the medical treatment focused on olfaction remained the same, contrary to previous olfactory training work [29][30]. In this context, solid and moderate relationships obtained between change in TDI, I, and depression severity suggest that olfaction is related even to very subtle changes in mood.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…However, according to the previously mentioned scale, a signi cant percentage of the present sample (one-third of the entire sample) was classi ed as depressed. That could probably explain why the depression severity before and after the medical treatment focused on olfaction remained the same, contrary to previous olfactory training work [29][30]. In this context, solid and moderate relationships obtained between change in TDI, I, and depression severity suggest that olfaction is related even to very subtle changes in mood.…”
Section: Discussioncontrasting
confidence: 60%
“…Previous studies demonstrated that dysosmic patients can bene t from olfactory training to improve their olfactory abilities and reduce their depression severity [29][30]. Odor identi cation is an olfactory dimension with a solid cognitive association [48] that has been consistently reported to be impaired in depression [16][17][18][19][20] probably because of the cognitive impairment in recurrent depression [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our sample, all subjects scored = < 9 points, suggesting none-to-minimal depression [ 34 ]. Subjects with low BDI scores are more likely to comply with the OT regimen, whereas those with high BDI scores may be discouraged to perform training and expect negative results [ 40 ]. Finally, the null results of OT on BDI symptoms and positive/negative affect may not be discernible, because both questionnaires (BDI and PANAS) relate to a shorter time frame than the period of OT used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that mood benefits from improving olfaction via regular olfactory exposure, so-called “olfactory training” (OT), leading to a decreased severity of depressive symptoms 30 , 31 . The question remains open as to whether this effect is caused by the positive impact of exposure to odors on mood 32 – 48 during OT or whether improvement in olfaction, even without OT, is directly related to the improvement in mood, possibly via neuroanatomical changes.…”
Section: Introductionmentioning
confidence: 99%